Kemampuan Guru dalam Memanfaatkan Lingkungan Sekolah sebagai Sumber Belajar melalui Kegiatan Buzz Group Discussion di TK Setia Kawan - Marliani, Marliani (CV. Creative Tugu Pena, 2022)
This research is designed in the form of School Action Research which is planned to be carried out in two cycles. The subjects of this study were teachers at Setia Kawan Kindergarten which consisted of 7 teachers. The implementation of this research begins with data collection using the observation format for the implementation of the discussion, the assessment of the learning scenario assessment instrument and the assessment of the learning implementation assessment instrument. Data collection techniques used observation and documentation techniques, while the data collection tools consisted of an observation format for the implementation of discussion activities in small groups, learning scenario assessment formats, and learning implementation assessment formats. The data analysis used is descriptive qualitative analysis by describing the qualitative data that has been collected at the initial observation stage and the observation stage of the implementation of the action. The results of the assessment that in the observation aspect the average score was 64.29 with less criteria, increased to 79.17 with sufficient criteria and 87.71 with good criteria in the last cycle. Thus, the implementation of research through Buzz group discussion activities is proven to be able to improve the ability of teachers at Setia Kawan Kindergarten in empowering the environment as a learning resource. Keywords: Buzz Group Discussion, Utilizing School Environment, Teachers Competence